Two Different Forms of Arousal in Drosophila are Independently and Oppositely Regulated by the Dopamine D1 Receptor DopR via Distinct Neural Circuits - Lebestky, Tim J. (2009)
Arousal is fundamental to many behaviors, but whether it is unitary, or whether there are different types of behavior-specific arousal, has not been clear. In Drosophila, dopamine promotes sleep-wake arousal. However there is conflicting evidence regarding its influence on environmentally stimulated arousal. Here we show that loss-of-function mutations in the D1 dopamine receptor DopR enhance repetitive startle-induced arousal, while decreasing nocturnal arousal (i.e., increasing sleep). These two types of arousal are also inversely influenced by cocaine, whose effects in each case are opposite to, and abrogated by, the DopR mutation. Selective restoration of DopR function in the central complex rescues the enhanced stimulated arousal but not the increased sleep phenotype of DopR mutants. These data provide evidence for at least two different forms of arousal, which are independently regulated by dopamine in opposite directions, via distinct neural circuits.